2021
DOI: 10.1177/0886260521997448
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Peers and Prevention: Network Patterns of Sexual Violence Attitudes and Bystander Actions

Abstract: Peer sexual violence is a significant social problem that affects adolescents and can lead to negative mental health and developmental consequences. Peers are a significant source of influence for adolescent behavior. For example, recent studies show training teens to be bystanders can be an effective prevention strategy to reduce peer violence and harassment. Peers can also promote risky behaviors including substance use and violence. The current study examined how sexual violence-specific risk and protective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 89 publications
1
8
0
Order By: Relevance
“…A point was subtracted from the score if participants acted negatively (behaviors a and b) and added to the score if participants acted positively (behaviors c, d, e, and f). Thus, final scores for each situation ranged from −2 to 4 (Banyard et al, 2021). Analyses of these outcomes were performed on smaller subsamples of participants who indicated opportunity and thus findings may be less stable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A point was subtracted from the score if participants acted negatively (behaviors a and b) and added to the score if participants acted positively (behaviors c, d, e, and f). Thus, final scores for each situation ranged from −2 to 4 (Banyard et al, 2021). Analyses of these outcomes were performed on smaller subsamples of participants who indicated opportunity and thus findings may be less stable.…”
Section: Methodsmentioning
confidence: 99%
“…We used the work of Banyard and colleagues (Banyard et al, 2014) as a base as well as adaptations of this work for high school samples by Coker and colleagues (Coker et al, 2019), and validity was confirmed in other analyses using this data set (Banyard et al, 2021). We chose the specific bystander situations included by drawing upon recent work on high school students as bystanders to dating violence, sexual harassment and violence, and stalking (Edwards et al, 2017).…”
Section: Bystander Behaviormentioning
confidence: 99%
“…Peers may also permit individuals to engage in inappropriate behavior as they may provide support for neutralizing beliefs, the perpetrator may blame others for their behavior, and/or they may not realize the cumulative effect of small offenses (Wortley, 2016). Prevention efforts in the context of this type of sexual offending should aim to engage peers in the push against sexually harmful behavior, enhance self-esteem and social skills, and develop peer resistance strategies (Banyard et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…On the flip side, having peers who are supportive of bystander norms is related to use of bystander behaviors (Hoxmeier et al, 2018). In fact, Banyard et al (2021) found a positive association between an individual's and their peers' use of reactive bystander behaviors. Friend groups tend to have similar norms and behaviors (Mumford et al, 2017).…”
Section: Association With Aggressive Friendsmentioning
confidence: 97%